2017
DOI: 10.1074/jbc.m117.787739
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species trigger Parkin/PINK1 pathway–dependent mitophagy by inducing mitochondrial recruitment of Parkin

Abstract: Defective mitophagy linked to dysfunction in the proteins Parkin and PTEN-induced putative kinase 1 (PINK1) is implicated in the pathogenesis of Parkinson's disease. Although the mechanism by which Parkin mediates mitophagy in a PINK1-dependent manner is becoming clearer, the triggers for this mitophagy pathway remain elusive. Reactive oxygen species (ROS) have been suggested as such triggers, but this proposal remains controversial because ROS scavengers fail to retard mitophagy. Here we demonstrate that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
125
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(135 citation statements)
references
References 51 publications
10
125
0
Order By: Relevance
“…Our results indicated that rhSTC1 treatment decreased the expression of Drp1 and the translocation of Drp1 to mitochondria. Fourth, other researchers found that ROS as a trigger for the generation of PINK1-Parkin mediated mitophagy and the inhibition of ROS generation significantly decreased the expression of Parkin and its translocation to mitochondria [34]. This was also consistent with our results that rhSTC1 treatment decreased ROS generation and then probably decreased mitophagy and mitophagy-related proteins.…”
Section: Keap1supporting
confidence: 92%
“…Our results indicated that rhSTC1 treatment decreased the expression of Drp1 and the translocation of Drp1 to mitochondria. Fourth, other researchers found that ROS as a trigger for the generation of PINK1-Parkin mediated mitophagy and the inhibition of ROS generation significantly decreased the expression of Parkin and its translocation to mitochondria [34]. This was also consistent with our results that rhSTC1 treatment decreased ROS generation and then probably decreased mitophagy and mitophagy-related proteins.…”
Section: Keap1supporting
confidence: 92%
“…Excessive ROS trigger the opening of the MPTP and activate PINK1/Parkin‐mediated mitophagy . To investigate whether ROS play a role in PARP‐mediated changes in ΔΨm, we measured ROS production in H/R‐treated H9C2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…At the beginning of myocardial reperfusion, a large amount of ROS is produced from a variety of sources including extracellular and intracellular actions . ROS activate PINKI/Parkin‐mediated mitophagy by promoting the opening of the MPTP and disrupting ΔΨm . ROS also function as a direct signal to induce mitophagy .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations